Comparative effectiveness of demonstration using hybrid simulation versus task-trainer for training nursing students in using pulse-oximeter and suction: A randomized control trial. (March 2022) - Arabpur, Alireza; Farsi, Zahra; Butler, Samantha; Habibi, Hengameh
Abstract: Background: Educating medical professionals on the emergency protocol for cardiac arrest can improve survival. Objectives: This study aimed to compare the effectiveness of demonstration using hybrid simulation versus task-trainer for training nursing students in using pulse-oximeter and suction following cardiac arrest. Design: This randomized clinical trial was conducted in 2019. Setting: The study was carried out in a nursing school in Tehran, Iran. Participants: Nursing students. Methods: Nursing students were recruited and randomly assigned to one of three groups: a demonstration training group using hybrid simulation (standardized patient and task-trainer) in a transport ambulance (N = 15), a demonstration training group using task-trainer in skill lab (N = 15), and a control group (N = 15). No education was performed in the control group. Each student was evaluated pre and post-training on the use of a pulse-oximeter along with knowledge and skill of suction. Students were evaluated using a knowledge questionnaire and an appraisal checklist. Results: All three groups increased their abilities in using pulse-oximeter and suction two weeks post-training session. The trial groups demonstrated better scores on the knowledge questionnaire and skill checklist in comparison to the control group. However, hybrid simulation and task-trainer groups showed no significant difference in knowledge and skill on the use of two modes. Conclusion: The use of demonstration using hybrid simulation in a transport ambulance and task-trainer in skill lab were equally effective in educating nursing students on the use of pulse-oximeter and suction following a cardiac arrest.